Karakteristik Mineralogi Dan proses Pengendapan Emas Pada Endapan Emas-Perak Epitermal Gunung Pongkor, Jawa Barat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
The Pongkor gold-silver deposit, formed at Pliocene age (2.05 ± 0.05 Ma) is the largest low-sulfidation epithermal precious metal deposit in Java. It consists of more than nine major subparallel quartz-adularia-carbonate veins. Vein Will records five paragenetic sequences, dominated by calcite in the early stage and quartz in the later stages of hydrothermal evolution. The sulfide association as the main gold carrier is dominated by pyrite, chalcopyrite, sphalerite, ±galena. Minor phases are silver-rich sulfides and sulfosalts, such as acantite-aguilarite, polybasite-pearceite, famatinite, proustite, tetrahedrite. Gold occurs as electrum and uyienbogaardtite. Microthermometric measurements result that the hydrothermal solution indicates low salinity (0 vt,t.% NaC7 equivalent) with a formation temperature around 220°C. Primal), gold deposition is mostly controlled by boiling and mixing between low and high temperature fluids.Deep supergene enrichment of both gold and silver seems to be critical for making Pongkor an economic ore deposit. Keywords: epitermal, boiling, pengkayaan supergen, Pongkor, emas